Fragrance carrier based on zeolite-A modified bentonite as a controlled release system in air freshener applications - Kusrini, Eny; Anwar Usman,; Ayuningtyas, Karina; Wilson, Lee D.; Putra, Nandy; Prasetyo, Agus Budi; Rahman, Arif; Nugrahaningtyas, Khoirina Dwi; Santosa, Sri Juari; Noviyanti, Atiek Rostika (Penerbit Universiti Kebangsaan Malaysia, 2024)
The quality of air fresheners with low cost production can be improved by using a carrier matrix such as synthetic zeolite to increase the long-lasting properties of fragrance product by encapsulation technique. The zeolite A is considerd as a safe core fragrance carrier matrix to be able to release volatile fragrance from their pores when exposed to atmospheric humidity at room temperature. Zeolite A was synthesized from natural kaolin and was formed into tube pellets with bentonite (20 wt.%) as binder to produce zeolite A-bentonite (ZAB) cylindrical pellets composite and used as a fragrance carrier matrix with a rose essential oil (Rose damascena Mill.) as parfume model. The fresh bentonite can also adsorb the rose essential oil with adsorption capacity of 1.745 g/g bentonite (74.5%). Effects of chemical activation on zeolite-A using acid (HCl) of 0.1 M and base (NaOH) of 0.1 M were studied. The ZAB tube pelletes were found to have high adsorption efficiencies of rose essential oil. ZAB4 has the highest efficiency and was used for regeneration test studies that was carried out over 10 cycles using HCl and NaOH, where the adsorption efficiency was 94.5 and 75.4%, respectively. The activated ZAB4 composite using HCl has a long life time until more than 5 weeks and more than 10 regeneration cycles. This fragrance carrier matrix based on ZAB has significant potential for extended carrier fragrance system.